Analisis Kinerja Keuangan dan Dampaknya terhadap Kualitas Layanan Dasar di Desa Jamburnauli Kecamatan Tarutung KabupatenTapanuli Utara - Monika Flora Manik; Apriani Hutabarat; Rini Khairani Harahap; Ivan R Ventris Siahaan; Kevin Lejon Simamora (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to examine the financial performance of Jamburnauli Village and its influenceonthequalityofbasicpublicservicesprovidedtothecommunity.Theresearch employs a qualitative method with a descriptive approach through interviews with the Village Head and literature reviews related to village financial management and public service delivery. The findings indicate that the realization of the Village Fund reached 100% and was utilized for the construction of farm roads, irrigation channels, bridges, cleanwaterfacilities,aswellasvarioussocialprogramssuchasagriculturalassistance, maternal and child health support, and cash transfers for households experiencing extreme poverty. The use of local materials also enhanced budget efficiency, allowing programstobeimplementedmoreoptimally.However,thevillage’sfiscalindependence remainslowduetolimitedlocallygeneratedrevenueandthenewlyestablishedBUMDes. Budget transparency and internal control mechanisms demonstrate accountable financialgovernanceandsupportimprovementsinbasicservices.Overall,effectiveand efficientfinancialperformancehascontributedsignificantlytoimprovinginfrastructure, health services, education, and administrative services in Jamburnauli Village.